The Piercing of Corporate Veil Doctrine dalam Pertanggungjawaban Perdata Perseroan Terbatas di Indonesia - Lukas Natama Putra Mahulae; Yunanto Yunanto (Journal of Creative Student Research, 2026)
This study examines the application of the The Piercing of Corporate Veil doctrine in the civil liability framework of Limited Liability Companies in Indonesia. The doctrine serves as an exception to the principle of limited liability, allowing courts to impose personal liability on shareholders, directors, commissioners, parent companies, or controlling parties who misuse the corporate entity for unlawful purposes. This research employs a normative legal method using statutory, conceptual, and case approaches. The findings indicate that the doctrine has been recognized in Indonesian company law, particularly through several provisions of Law Number 40 of 2007 concerning Limited Liability Companies. Its implementation extends beyond shareholders to encompass directors, commissioners, controlling shareholders, holding companies, and individual companies when evidence demonstrates abuse of legal entity status, commingling of assets, ultra vires acts, bad faith conduct, or unlawful corporate control. The study concludes that the doctrine functions as an essential legal mechanism for balancing investor protection with accountability, legal certainty, and justice for creditors and third parties harmed by corporate misconduct.